Courageous conversations about race a field guide for achieving equity in schools - Singleton, Glenn E. (Glenn Eric) (Corwin, a Sage Company, 2015)
Create a systemwide plan for transforming the district office, schools, and classrooms into places that truly support ALL students achieving their highest levels! This updated edition of the bestseller continues to explain the need for candid, courageous conversations about race so that educators may understand why achievement inequality persists and learn how they can develop a curriculum that promotes true educational equity and excellence. NEW! Revised Courageous Conversation Compass NEW! Racial autobiographies NEW! Case study on St. Paul Public Schools, which has stayed on track with the Courageous Conversation protocol and framework NEW! Links to video segments of the author describing the work REVISED! Activities and checklists for school and district leaders REVISED! Action and implementation steps.